Formation of voids in composite laminates: Coupled effect of moisture content and processing pressure. Issue 2 (26th February 2014) - Anderson, J.P.; Altan, M.C.
<x xml:space="preserve">Abstract</x> Void formation as a result of prepreg moisture content and processing pressure during cure was experimentally investigated in thermosetting composite laminates. This was achieved by determining the void contents of eight‐ply laminates fabricated from TenCate® BT250/7781 E‐glass/epoxy prepreg at processing pressures of 1.7, 3.0, 4.4, and 5.8 atm. At each processing pressure, three types of laminates were fabricated using: (i) unconditioned prepregs (direct from the storage bag); (ii) prepregs conditioned at 25% relative humidity; and (iii) 99% relative humidity. Dynamics of prepreg moisture uptake during conditioning was measured using a moisture analyzer and was shown to exhibit Fickian diffusion behavior. The void contents of the cured laminates were found to vary from 1.6% to 5.0% depending on humidity environment the prepregs were exposed and the pressure applied during fabrication. The void contents of all laminates were observed to approach an asymptotic value of ∼1.6% as pressure was increased. The experimental results indicated the processing pressure applied during fabrication was increasingly carried by the fiber bed, reducing resin pressure during cure. Therefore, an enhanced void formation model was proposed through the addition of a pressure reduction factor and an asymptotic void content term. The proposed model was found to accurately predict the void content of laminates made of prepregs exposed to constant/varying humidity environments and fabricated at a wide range of processing pressures. POLYM. COMPOS., 36:376–384, 2015. © 2014 Society of Plastics Engineers